2018
DOI: 10.3382/ps/pey212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acidified drinking water on growth performance and gastrointestinal function of broilers

Abstract: The ban on the use of antibiotic feed additives as growth promoters compelled the researchers for exploring the future utility of other alternatives. This experiment was designed to evaluate the effect of acidified drinking water on growth performance, gastrointestinal pH, digestive enzymes, intestinal histomorphology, and cecum microbial counting of the broiler chicken. A total of 540 one-day-old male broilers (Arbor Acre) were randomly assigned to 5 treatments, with 6 replicates of 18 chicks per replicate. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 50 publications
1
14
0
1
Order By: Relevance
“…Pullorum challenge on growth performance of broilers. The positive effect of OA supplementation on performance was comparable to virginiamycin in this study and to other antibiotics in a previous study (Hamid et al, 2018). The antimicrobial activity of OA and its effects on intestinal morphology could partly explain the growth improvement (Suiryanrayna and Ramana, 2015; Khan and Iqbal, 2016).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Pullorum challenge on growth performance of broilers. The positive effect of OA supplementation on performance was comparable to virginiamycin in this study and to other antibiotics in a previous study (Hamid et al, 2018). The antimicrobial activity of OA and its effects on intestinal morphology could partly explain the growth improvement (Suiryanrayna and Ramana, 2015; Khan and Iqbal, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Pullorum challenge-induced enhancement of lysine degradation, indicating that intestinal flora are probably involved in the modulation of OA, because conversion of lysine into piperidine is dependent on intestinal flora. Acidified water inhibited aerobic bacterial count and Escherichia coli population in cecum contents of broilers, but did not change the pH of cecum (Hamid et al, 2018). In fact, we also analyzed the cecal microbiome but failed to observe any significant change in alpha-diversity indices of cecal microbiota, differentially abundant phyla, or family across the groups on day 42.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is more effective for young poultry that have an unmatured digestive system ( Andrys et al., 2003 ). Moreover, we found that acidified drinking water, which was acidified with a liquid acidifier (Lupro-Mix NC, produced by BASF Co., Ltd., consisting of propionic acid, ammonium propionate, formic acid and ammonium formate as active ingredients), could improve growth performance, compensate for gastric acidity, and control pathogenic bacteria in broilers ( Hamid et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants are chemical compounds that can be used to protect biological components such as lipids, proteins, vitamins and DNA from oxidation (Mbah et al, 2019). In addition, asam kandis is able to act as a natural acidifier that can improve performance through decreasing gastrointestinal pH which is suitable to support the digestive enzymes and reduce the pathogenic bacteria in the intestine (Hamid et al, 2018;Kopecký et al, 2012). Hydroxy citric acid is the main organic acid in asam kandis that can cause a decrease in pH value (Onakpoya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%